PREVENTION OF NON-COMMUNICABLE DISEASES (NCDS) FOR A HEALTHIER AND MORE PRODUCTIVE SOCIETY - Arwani Arwani; Lanny Sunardjo; Edy Susanto; Irmawati Irmawati; Sri Sumarni; Endah Aryati Eko N; Gatot Murti Wibowo; Ahmad Riadi; Umi Margi Rahayu (Poltekkes Kemenkes Semarang, 2024)
One Diabetes Mellitus (DM) is one of the metabolic diseases characterized by high blood sugar levels or hyperglycemia, which occurs due to insulin secretion failure. This disease is chronic with the number of sufferers continuing to increase in the world along with increasing population, age, prevalence of obesity and decrease in physical activity. The purpose of community service as early detection of non-communicable diseases at chronic risk and strengthening with health education. The target in community service is those aged between 45-50 years. The results of community service show that the majority of measurements of abnormalities of uric acid, cholesterol and blood pressure are within normal ranges While health education shows the knowledge of health cadres in a very good range.Â